Virtual education in contexts of digital inequality: the case of connectivity among students at a public university in Lima - Correa Flores , Wilder Ulises (2025)
The main objective of this study was to analyze the relationship between virtual education and connectivity among students at a public university in Lima. The research was conducted using a quantitative approach, using a basic, non-experimental, descriptive-correlational design. Two structured surveys were used to collect data, which separately assessed the dimensions of virtual education and connectivity. The sample was purposive and comprised 80 university students. The reliability of the instruments was verified using Cronbach's alpha coefficient, obtaining a value of 0.858 for the questionnaire referring to virtual education and 0.731 for the one addressing connectivity, ensuring adequate levels of internal consistency. Data processing was performed using descriptive and inferential statistical analyses using SPSS software. Spearman's rho correlation was applied to test hypotheses, identifying statistical significance in both variables with p values less than 0.05. This confirms the existence of a positive, strong, and significant relationship between the perceived quality of virtual education and students' level of connectivity.